The Influence of Cesarean Section on the Composition and Development of Gut Microbiota During the First 3 Months of Life - Long, Gao; Hu, Yuting; Tao, Enfu; Chen, Bo; Shu, Xiaoli; Zheng, Wei; Jiang, Mizu (Frontiers in Microbiology, 2021)
The intestinal microbiota has emerged as a critical regulator of growth and development in the early postnatal period of life. Caesarean section (CS) delivery is one of the strongest disrupting factors of the normal colonization process and has been reported to a risk factor for disorders in later life. In this study, we dynamically and longitudinally evaluated the impact of CS on the initial colonization pattern and development of gut microbiota by sixteen healthy Chinese infants with fecal samples collected at nine time points (day 5, day 8, day 11, week 2, week 4, week 6, week 7, month 2 and month 3) during the first three months of life. The V3-V4 regions of 16S rRNA gene were analyzed by Illumina sequencing. In comparison with vaginally delivered (VD) infants, infants born by CS showed decreased relative abundance of Bacteroides, Parabacteroides, and enrichment of Clostridium_sensu_stricto_1, Enterococcus, Klebsiella, Clostridioides, and Veillonella. Most interestingly, Firmicutes/Bacteroidetes ratio was found significantly higher in the CS group than in the VD group from day 5 until month 3. Besides, the results of microbial functions showed that VD group harbored significantly higher levels of functional genes in Vitamin B6 metabolism at day 5, day 8, week 2, week 4, week 6, week 7, month 2 and month 3, and taurine and hypotaurine metabolism at day 5, while the phosphotransferase system and starch and sucrose metabolism involved functional genes were plentiful in CS group at day 11, week 2, week 4, week 6, week 7 and month 2, and at week 2, week 7 and month 2, respectively. Our results establish a new evidence that CS affected the composition and development of gut microbiota in the first three months and provide a novel insight into strategies for CS-related disorders in later life.